Ultrasound Assessment of Carotid Intima-Media Thickness: Comparison between Diabetes and Nondiabetes Subjects, and Correlation with Serum Vitamin D - Sameeah Abdulrahman Rashid (Radiology Research and Practice)
Background and Objective. Diabetes contributes to considerable morbidity and mortality through vascular complications. Sonographic evaluation of carotid intima-media thickness (CIMT) is accepted as a surrogate marker for atherosclerosis. The aim of this study was to find out the difference in the CIMT between diabetes and nondiabetes and determine its correlation with serum vitamin D and some other modifiable and nonmodifiable cardiovascular risk factors. Methods. This multicenter cross-sectional study was performed on two groups of adults (nondiabetes and type 2 diabetes) of various ages, sexes, and body mass index (BMI). CIMT for each side was measured at three segments using high-resolution ultrasound, and the mean of both sides was determined. Comparison was made between each group, and the association of CIMT with each of age, sex, BMI, serum vitamin D status, smoking, and physical activity status was studied. The chi-square test was used to compare categorical data, and binary logistic regression was utilized to ascertain the relationship between CIMT and the study variables. Results. A significant difference was observed between the CIMT of the diabetes and nondiabetes group, average CIMT was 0.82 ± 0.23 mm vs. 1.12 ± 0.24 mm for the nondiabetes and diabetes group, respectively, with P value <0.005. No significant correlation was observed between serum vitamin D level and CIMT neither in the study group as a whole nor in either subgroup; however, a significant association was observed between CIMT with each of age, sex, BMI, smoking, and physical activity status. Conclusion. Ultrasound is a sensitive tool for CIMT evaluation. Diabetes has a 5.4-fold higher risk of having high CIMT. Serum vitamin D level showed no significant influence on CIMT. Smoking, BMI, and physical activity are among the modifiable risk factors with significant influence on CIMT.